2023
DOI: 10.1002/cncr.35071
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic germline variants in patients with endometrial cancer of diverse ancestry

Ying L. Liu,
Sushmita Gordhandas,
Kanika Arora
et al.

Abstract: BackgroundRacial disparities in outcomes exist in endometrial cancer (EC). The contribution of ancestry‐based variations in germline pathogenic variants (gPVs) is unknown.MethodsGermline assessment of ≥76 cancer predisposition genes was performed in patients with EC undergoing tumor‐normal Memorial Sloan Kettering Cancer Center Integrated Mutation Profiling of Actionable Cancer Targets sequencing from January 1, 2015 through June 30, 2021. Self‐reported race/ethnicity and Ashkenazi Jewish ancestry data classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…56 Additionally, the MMRdeficient/MSI-H molecular subtype is associated with Lynch syndrome, an inherited cancer predisposition syndrome caused by germline pathogenic variants (gPVs) in the MMR genes, and ancestry-based variations in gPV and Lynch syndrome have been observed. 57 These ancestry-based tumor molecular differences may influence the racial/ethnic disparities in EC outcomes and are important to address in clinical trial accrual and efforts to improve health equity.…”
Section: Therapeutic Implications Of the Ec Molecular Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Additionally, the MMRdeficient/MSI-H molecular subtype is associated with Lynch syndrome, an inherited cancer predisposition syndrome caused by germline pathogenic variants (gPVs) in the MMR genes, and ancestry-based variations in gPV and Lynch syndrome have been observed. 57 These ancestry-based tumor molecular differences may influence the racial/ethnic disparities in EC outcomes and are important to address in clinical trial accrual and efforts to improve health equity.…”
Section: Therapeutic Implications Of the Ec Molecular Subtypesmentioning
confidence: 99%
“…On the other hand, high TMB (≥10 mut/Mb) molecular subtypes such as MMR‐deficient/MSI‐H or POLE were less common in Black as compared with White patients with EC, and less likely to have actionable alterations including high TMB/MSI, which would preclude use of breakthrough treatments such as ICB 56 . Additionally, the MMR‐deficient/MSI‐H molecular subtype is associated with Lynch syndrome, an inherited cancer predisposition syndrome caused by germline pathogenic variants (gPVs) in the MMR genes, and ancestry‐based variations in gPV and Lynch syndrome have been observed 57 . These ancestry‐based tumor molecular differences may influence the racial/ethnic disparities in EC outcomes and are important to address in clinical trial accrual and efforts to improve health equity.…”
Section: Heterogeneity Within the Ec Molecular Subtypesmentioning
confidence: 99%
“…11 Although it is tempting to wonder whether non-English-speaking patients are less likely to be referred for genetic testing, 25% of patients who identified as Hispanic, 14% as Asian, and 1.2% as Black/AA selected a language other than English as their preferred language. 8 Nevertheless, in the cohort reported by Liu et al, Black/ AA patients had the lowest referral rates to clinical genetics, and patients of Asian ancestry had the highest rates. 8 Other studies have also shown that when patients are referred for counseling, race and sociodemographic factors did not affect the likelihood of making an appointment.…”
mentioning
confidence: 91%
“…8 Nevertheless, in the cohort reported by Liu et al, Black/ AA patients had the lowest referral rates to clinical genetics, and patients of Asian ancestry had the highest rates. 8 Other studies have also shown that when patients are referred for counseling, race and sociodemographic factors did not affect the likelihood of making an appointment. 12 This suggests that clinician communication with the patient and referral are a crucial strategy for increasing genetic counseling and screening in minority or underserved populations.…”
mentioning
confidence: 91%
See 1 more Smart Citation